2022
DOI: 10.48550/arxiv.2208.02257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mystery in Gaia DR3 triples: occurrence rates, orientations, and eccentricities of wide tertiaries around close binaries

Abstract: The formation of close binaries has been an open question for decades. A large fraction of close binaries are in triple systems, suggesting that their formation may be associated with the Kozai-Lidov mechanism. However, this picture remains under debate because the configurations of many observed triples are unlikely to trigger the Kozai-Lidov mechanism. In this paper, we use the close binary samples, including eclipsing, spectroscopic, and astrometric binaries, from Gaia Data Release 3 to investigate the myst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This enhancement factor is significantly lower than the 2.28 ± 0.10 measured by Hwang (2022). However, the comparison is not necessarily valid: note that Hwang (2022) applied corrections for separation-dependent incompleteness which we have not applied.…”
Section: Triple Systemsmentioning
confidence: 57%
See 2 more Smart Citations
“…This enhancement factor is significantly lower than the 2.28 ± 0.10 measured by Hwang (2022). However, the comparison is not necessarily valid: note that Hwang (2022) applied corrections for separation-dependent incompleteness which we have not applied.…”
Section: Triple Systemsmentioning
confidence: 57%
“…Tokovinin et al (2006) estimated that the frequency of tertiary companions to solar-type bi-nary systems with P orb < 3 days may be as high as 96 per cent. Hwang (2022) found that the wide (10 3 -10 4 au) tertiary frequency for targets in the Gaia eclipsing binary sample is 2.28 ± 0.10 times higher than the frequency of wide binary stars. For Gaia eclipsing binaries with periods < 3 days the tertiary frequency was approximately 12-15 per cent.…”
Section: Triple Systemsmentioning
confidence: 81%
See 1 more Smart Citation